Correlation of High sensitivity C-reactive Protein Levels with Body Mass Index in a Group of Adults in Erbil City - Salam Naser Zangana; Namir G Al-Tawil; Suhad Ali Khazaal (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background and Objectives: The prevalence of overweight and obesity is increasing worldwide. Obesityis related to morbidity and mortality. High sensitivity C - reactive protein (hs-CRP) is an importantinflammatory marker to predict cardiovascular diseases. This study aims to correlate between hs-CRP levelsand BMI among healthy adults.Materials and Methods: A cross-sectional study was conducted on 200 healthy adults from May 2019 toOctober 2019. The study population was divided into four groups based on BMI; normal, overweight, obeseI, and obese II. Hs-CRP level was measured in all groups. Multiple linear regression analysis was done tofind out the independent factors affecting hs-CRP.Results: Out of 200 participants, 56 (28%) had normal BMI, 43(21.5%) were overweight, 57(28.5%) wereobese group I and 44 (22%) were obese group II. The mean hs-CRP of the normal weight and overweightparticipants was 1.03 mg/dl and 1.37 mg/dl respectively (p= 0.725), then there was a marked increase to3.75 mg/dl and 7.69 mg/dl among the obese I and obese II participants respectively (p < 0.001). A positivesignificant correlation was found between the hs-CRP levels and the BMI (r = 0.436, p < 0.001). The onlyfactor that was independently associated with the high hs-CRP was the BMI (B = 0.357, p < 0.001).Conclusion: Rising BMI was significantly correlated with hs-CRP. The higher the BMI, the higher willbe plasma hs-CRP levels, suggesting the presence of chronic systemic inflammation which might lead tocardiovascular events in the future.